KONTROL KOMPLEMETER YANG OPTIMAL UNTUK SISTEM LTI STABIL POSITIF - Nurweni Putri; Iswan Rina (Department of Mathematics, Hasanuddin University, 2021)
The optimal control problem is defined as a problem in selecting a controller u(t) in a continuous linear system, so that it can provide the optimum value for a given objective function. The u(t) controller is expected to control the system so that it produces the desired output. In this research, it will be studied about how to select and construct the optimal controller u(t) in the Linear Time Invariant MIMO system positive stable, so that the given system will remain positive when given constant disturbance